2014
DOI: 10.1063/1.4863506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gap spacing on the characteristics of Trichel pulse generated in point-to-plane discharge gaps

Abstract: In this paper, the specific characteristics of the Trichel pulse generated in wide point-to-plane discharge gaps are investigated and compared with those of the currents generated in narrow gaps. A set of empirical formulas are derived to describe the specific characteristics. The influence of the gap spacing both on the current characteristics and on the coefficients of the formulas is studied. Based on the experiment results, an improvement is made to the space charge calculation method proposed by Lama and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“… 7 , 8 developed a similar theory for negative corona in oxygen that emphasizes the importance of the relatively wide plasma region which brings the electric field close to zero over much of the cathode region, and the crucial role played by attachment in converting electrons to negative ions, freezing the electric field formation in place. The above theory has been generally accepted by many researchers 9 12 . In recent years, there are still some numerical simulations performed on the evolution of negative corona discharge and the behaviors of Trichel pulses 13 17 .…”
Section: Introductionmentioning
confidence: 87%
“… 7 , 8 developed a similar theory for negative corona in oxygen that emphasizes the importance of the relatively wide plasma region which brings the electric field close to zero over much of the cathode region, and the crucial role played by attachment in converting electrons to negative ions, freezing the electric field formation in place. The above theory has been generally accepted by many researchers 9 12 . In recent years, there are still some numerical simulations performed on the evolution of negative corona discharge and the behaviors of Trichel pulses 13 17 .…”
Section: Introductionmentioning
confidence: 87%
“…where k c is a constant, r is needle tip radius, S is the pointto-plane spacing. On the other hand, He et al [55,56] proposed another type of f -V a based on their experimental observation,…”
Section: Frequency Characteristicsmentioning
confidence: 99%
“…Regardless of forward discharge or backward discharge, the discharge current shows a double exponential pulse characteristic. Early studies have shown that the discharge pulse current directly reflects the behaviour of space charge and the physical process of discharge during discharge development [16, 17]. In order to analyse the influence of voltage frequency on the surface discharge of PEEK material, the current pulse parameters [1820], i.e.…”
Section: Experiments Results and Analysismentioning
confidence: 99%